Pembuatan Antiserum dan Kajian Serologi Virus Penyebab Penyakit Daun Keriting Kuning Cabai - Sri Sulandari; Rusmilah Suseno; Sri Hendrastuti Hidayat; Soemartono Sosromarsono; Jumanto Harjosudarmo (Universitas Gadjah Mada, 2004)
Virus identification based on the serological assay has been widely applied as a tool for plant virus detection. The aims of this research is to produce antiserum of the Pepper yellow leaf curl virus by rabbit immunization using purified gcminivirus of Segunung isolate. Identification of the virus was done by using modified I-ELISA and DIBA methods and also by using western blott. I-ELISA and DIBA methods were able to detect the geminivirus in the infected samples. The reactivity of antiserum was found to be similar amontI pepper isolates from different location (Segunung, Yogyakarta, Cugenang, and Lembang) ana those from different hosts (pepper, tobacco, tomato and Ageratum conyzoides) The antiserum could also be used for detection and identification of the Pepper yellow leaf curl virus in its vector. A single insect vector is sufficient for the detection of virus properly. The detection of geminivirus in its vector is very useful because it can be used to study the epidemic of the disease in the field. The I-ELISA and DIBA methods are very useful as tools for detecting the geminivirus. The methods are very easy to be carried out, fastly, and need only a minimum cost on operation. Geminivirus could also be identified by western blott analysis.